Organic electroluminescent device, display device, lighting device
By using organic materials with multiple coordination capabilities and electrode structures of magnesium, silver and aluminum in the organic electroluminescent industry, the problems of difficult to balance high characteristics and economics in the prior art are solved, and good light emission and atmospheric stability are achieved, and suitable for flexible display and lighting equipment.
Patent Information
- Application Number
- JP2021071277
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-20
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2041-04-20
AI Technical Summary
The prior art is difficult to develop high-characteristic and economical organic electrosilicons, especially in obtaining good luminescent performance and atmospheric stability.
An organic material with multiple coordination capabilities is used as the electron injection layer, combined with an electrode structure of magnesium, silver and/or aluminum, to form excellent electron injection performance through coordination bonds, and to improve air stability by controlling the ratio of magnesium and layer thickness.
High-quality light emission and excellent air stability are achieved, making the organic and electrical light emitting element suitable for flexible display and lighting equipment, extending the service life of the equipment.
Smart Images

Figure 0007657646000021 
Figure 0007657646000022 
Figure 0007657646000023
Abstract
Description
[Technical field]
[0001] The present invention relates to an organic electroluminescence (hereinafter, electroluminescence may be abbreviated as "electroluminescence" or "EL") element, a display device, and a lighting device. [Background technology]
[0002] Organic EL elements are thin, soft, and flexible. Furthermore, displays using organic EL elements are capable of displaying images with higher brightness and higher resolution than the currently mainstream liquid crystal display devices and plasma display devices. Furthermore, displays using organic EL elements have a wider viewing angle than liquid crystal display devices. For this reason, it is expected that displays using organic EL elements will be used more widely in the future as displays for televisions and mobile phones. Organic EL elements are also expected to be used as lighting devices.
[0003] An organic EL element is a laminate of a cathode, a light-emitting layer, and an anode. In an organic electroluminescent element, a light-emitting organic compound is excited by utilizing the energy generated when holes injected from an anode and electrons injected from a cathode are recombined to emit light. Since it is important that holes are injected from an anode and electrons are injected from a cathode smoothly, various materials for the hole injection layer and the electron injection layer have been studied to ensure smoother hole and electron injection. Recently, an organic electroluminescent element with a normal structure using polyethyleneimine or a compound modified with polyethyleneimine as a material for an electron injection layer that can be applied has been reported (see Non-Patent Documents 1 to 3). Similarly, Non-Patent Documents 4 to 6 have reported that phenanthroline derivatives having nitrogen atoms promote electron emission from metal atoms due to their high coordination ability with metal ions, and significantly lower the electron injection barrier at the electrode / organic layer interface, and that the use of a phenanthroline derivative between an electrode and an organic layer improves electron injection ability. Organic EL devices using compounds having a structure in which a nitrogen-containing amino group or the like is bonded directly or via another group to a group derived from an electron transporting compound as a material for the electron injection layer, or organic materials having an acid dissociation constant pKa of 1 or more have also been disclosed (see Patent Documents 1 to 3). However, organic electroluminescence devices in which the layers between the cathode and anode are all made of organic compounds are, in principle, prone to degradation by oxygen and water, and require strict sealing to prevent these from entering in. This makes the manufacturing process for organic electroluminescence devices complicated and is an obstacle to the development of flexible devices. In response to this, an organic-inorganic hybrid electroluminescent device (HOILED device) has been proposed, in which a part of the layer between the cathode and anode is made of inorganic oxide and the cathode is arranged on the substrate side (see Patent Document 4). In this device, by changing the hole transport layer and electron transport layer to inorganic oxide, it is possible to use conductive oxide electrodes such as FTO or ITO as the cathode and gold as the anode. This means that there are no longer any restrictions on the electrodes from the viewpoint of device operation. As a result, there is no longer a need to use metals with small work functions such as alkali metals and alkali metal compounds, and it is possible to emit light without strict sealing, which is a great contribution to flexible devices. This HOILED device is expected to develop as a candidate for an inverted structure organic EL device. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-157743 A [Patent Document 2] JP 2019-176093 A [Patent Document 3] JP 2019-179863 A [Patent Document 4] JP 2009-70954 A [Non-patent literature]
[0005] [Non-Patent Document 1] Tao Xiong et al., "Applied Physics Letters", Vol. 93, 2008, pp. 123310-1 [Non-Patent Document 2] Yinhua Zhou and 21 others, Science, No. 336, 2012, pp. 327 [Non-Patent Document 3] Jianshan Chen et al., Journal of Materials Chemistry, 2012, Vol. 22, pp. 5164 [Non-Patent Document 4] Hiroyuki Yoshida, Journal of Physical Chemistry (J. Phys. Chem. C20151194324459-24464), Vol. 119, 2015, p. 24459 [Non-Patent Document 5] Zhengyang Bin and 7 others, Nature Communications, Vol. 10, 2019, p. 866 [Non-Patent Document 6] Hirohiko Fukagawa and 8 others, Nature Communications, Vol. 11, 2020, p. 1 [Non-Patent Document 7] Herbert B. Michaelson, J. Appl. Phys., Vol. 48, 1977, p. 4729 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in view of the above-mentioned current situation, and aims to provide a flexible organic electroluminescence device with higher characteristics and lower cost, particularly, the invention is an invention that solves the problem of providing a device that can obtain good light emission and has excellent atmospheric stability. [Means for solving the problem]
[0007] The present inventors have conducted various studies on materials that improve the electron injection ability of an organic electroluminescent device that can provide good light emission. They have found that an organic electroluminescent device that can provide good light emission and also has excellent atmospheric stability can be obtained by forming an organic electron injection layer containing an organic material having a coordination site, such as an organic material capable of multidentate coordination that has an electron-donating nitrogen atom in a heterocycle, adjacent to a cathode of a given thickness that contains magnesium, which serves as the coordination site, and silver and / or aluminum in a given ratio.
[0008] The present invention has been completed based on the above findings, and the gist of the present invention is as follows. [1] An organic electroluminescent device having at least a pair of electrodes and an organic layer between them, the organic electroluminescent device having a cathode which is a layer containing magnesium and silver and / or aluminum, the volume ratio of magnesium being 2% or more and 30% or less, and having an average thickness of 40 nm or less, and an organic electron injection layer adjacent to the cathode which contains an organic material capable of forming a coordinate bond to a metal atom. [2] The organic electroluminescent device according to [1], wherein the organic electroluminescent device is an element in which a cathode is formed on a substrate. [3] A display device comprising the organic electroluminescent device according to [1] or [2]. [4] A lighting device comprising the organic electroluminescent element according to [1] or [2]. Effect of the Invention
[0009] The organic electroluminescence device of the present invention provides good light emission and has excellent atmospheric stability, and therefore can be used as a flexible organic electroluminescence device for display devices, lighting devices, and light sources. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic diagram showing an example of a laminate structure of an organic electroluminescent device according to the present invention. [Diagram 2] 1 is a schematic diagram showing an example of a laminate structure of an organic electroluminescent device according to the present invention. [Diagram 3] 1 is a schematic diagram showing an example of a laminate structure of an organic electroluminescent device according to the present invention. [Figure 4] 1 is a schematic diagram showing a layered structure of an organic electroluminescent device produced in Example 1. FIG. [Diagram 5] 1 is a schematic diagram showing a laminated structure of an organic electroluminescent device produced in Comparative Example 3. FIG. [Figure 6] 1 shows the results of observing the light emission state of the organic electroluminescent device produced in Example 1 after storing it for 65 hours in an environment of 85° C. and humidity of 85% without sealing. [Figure 7] 1 shows the results of observing the light emission state of the organic electroluminescent device produced in Example 2 after storing it for 65 hours in an environment of 85° C. and humidity of 85% without sealing. [Figure 8] 1 shows the results of observing the light emission state of the organic electroluminescent device produced in Example 3 after storing it for 65 hours in an environment of 85° C. and humidity of 85% without sealing. [Figure 9] 1 shows the results of observing the light emission state of the organic electroluminescent device produced in Example 4 after storing it for 65 hours in an environment of 85° C. and humidity of 85% without sealing. [Figure 10] 1 shows the results of observing the light emission state of the organic electroluminescent device produced in Comparative Example 1 after storing it for 65 hours in an environment of 85° C. and humidity of 85% without sealing. [Figure 11] 1 shows the results of observing the light emission state of the organic electroluminescent device produced in Comparative Example 3 after storing it for 65 hours in an environment of 85° C. and humidity of 85% without sealing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below along the layers of the organic electroluminescent device. "Organic EL element" The present invention is an organic electroluminescence element (organic EL element) having an organic layer including a light-emitting layer between a pair of electrodes, a cathode and an anode, characterized in that the cathode is a layer containing magnesium, silver and / or aluminum, and adjacent to the cathode is an organic electron injection layer containing an organic material capable of coordinating to a metal atom. With such a configuration, excellent electron injection properties can be obtained by the coordination bond between magnesium and the organic material capable of coordinating to a metal atom. In addition, by making a layer having an average thickness of 40 nm or less in which a small amount of magnesium is contained in the cathode together with silver and / or aluminum, an element having excellent atmospheric stability can be obtained while using magnesium with a small work function. Furthermore, an element having such a configuration has a longer life than the element having a metal oxide layer on the cathode described above. The mechanism is considered to be that magnesium has denser coordination bonds than an oxide layer, which leads to a strong and uniform reduction in the injection barrier and a reduction in the intrusion of oxygen and water from the outside. The organic EL element preferably has an inverted structure in which the cathode is on the substrate, but may have a forward structure in which the anode is disposed on the substrate. Also, the organic EL element may be a bottom emission element in which light is extracted from the substrate side, or a top emission element in which light is extracted from the top of the substrate.
[0012] Next, the organic EL device of the present invention will be described in detail with reference to examples. 1 and 2 are schematic cross-sectional views for explaining an example of the organic EL element of the present invention. Here, the configuration of an inverted structure is shown. The organic EL element 1 of this embodiment shown in FIGS. 1 and 2 has an emitting layer 7 between the cathode 3 and the anode 10. In the organic EL element 1 shown in FIGS. 1 and 2, an organic electron injection layer 5 is present adjacent to the cathode 3 between the cathode 3 and the emitting layer 7. In addition, an electron transport layer 6 and a hole blocking layer 11 are provided as necessary. A hole transport layer 8 and a hole injection layer 9 are provided between the emitting layer 7 and the anode 10. In addition, a metal oxide layer 4 may be used as a base for the cathode 3 in order to increase the stability of the cathode (FIGS. 4 and 5).
[0013] In this embodiment, an organic EL element 1 having an inverted structure is described as an example, but the organic EL element of the present invention may have a forward structure in which an anode is disposed between a substrate and an emitting layer. Even when the organic EL element of the present invention has a forward structure, an organic electron injection layer is provided between the cathode and the emitting layer adjacent to the cathode, as in the case of the inverted structure. Another example of the structure of the organic EL element of the present invention is the structure shown in FIG. 3. The materials, thicknesses and sealing of the layers constituting the organic EL element 1 described below are the same as those of the organic EL element having a forward structure, except for the material of the anode described later.
[0014] "substrate" The material of the substrate 2 may be a resin material, a glass material, or the like. Examples of the resin material used for the substrate 2 include polyethylene terephthalate, polyethylene naphthalate, polypropylene, cycloolefin polymer, polyamide, polyethersulfone, polymethyl methacrylate, polycarbonate, polyarylate, etc. When a resin material is used as the material for the substrate 2, it is preferable because an organic EL element 1 having excellent flexibility can be obtained. Examples of glass materials used for the substrate 2 include quartz glass and soda glass.
[0015] When the organic EL element 1 is of a bottom emission type, the material of the substrate 2 is a transparent substrate. When the organic EL element 1 is of a top emission type, not only a transparent substrate but also an opaque substrate may be used as the material of the substrate 2. Examples of opaque substrates include a substrate made of a ceramic material such as alumina, a substrate in which an oxide film (insulating film) is formed on the surface of a metal plate such as stainless steel, and a substrate made of a resin material.
[0016] The average thickness of the substrate 2 can be determined depending on the material of the substrate 2 and is preferably 0.1 to 30 mm, and more preferably 0.1 to 10 mm. The average thickness of the substrate 2 can be measured using a digital multimeter and a vernier caliper.
[0017] "cathode" The cathode 3 is formed on and in direct contact with the substrate 2 . The cathode 3 is a layer formed containing magnesium, silver and / or aluminum. It may contain either silver or aluminum, or it may contain both. In the cathode 3, the volume ratio of magnesium in the layer containing magnesium and silver and / or aluminum is 30% or less. With such a ratio, the element has excellent electron injection properties and also excellent atmospheric stability. The volume ratio of magnesium is preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less. In order to exhibit better electron injection properties, the volume ratio of magnesium is 2% or more, preferably 3% or more, and more preferably 4% or more.
[0018] The average thickness of the cathode 3 is 40 nm or less. With such a thickness, the element has excellent atmospheric stability. The average thickness of the cathode 3 is preferably 35 nm or less, and more preferably 25 nm or less. From the viewpoint of the conductivity of the electrode and manufacturing variations of the element, the average thickness of the cathode 3 is preferably 3 nm or more. More preferably, it is 5 nm or more, and even more preferably, it is 10 nm or more. The average thickness of the cathode 3 can be measured by a stylus step gauge or spectroscopic ellipsometry. These materials can be used as the anode material when the organic EL device of the present invention has a forward structure in which the anode is disposed between the substrate and the light-emitting layer. In this case, the average thickness of the anode is preferably the same as that of the cathode 3.
[0019] "Organic electron injection layer" The organic electron injection layer 5 improves electron injection by forming a complex with magnesium contained in the cathode 3. The organic electron injection layer 5 may be made of an organic material having coordination ability. Among them, a compound having a nitrogen atom-containing substituent is preferable, and a compound having a nitrogen atom-containing heterocyclic condensed ring structure is more preferable. For example, an organic material contained in the organic electron injection layer of the present invention may be a compound having a structure represented by the following general formula (1).
[0020] [ka]
[0021] (In general formula (1), X 1 , X 2 are the same or different and each represents a nitrogen atom, an oxygen atom, a sulfur atom, or a divalent linking group which may have a substituent. L represents a direct bond or a p-valent linking group. 1 represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3 m may be the same or different and represents a monovalent substituent. 1 ~m 3 R may be the same or different and represents a number from 0 to 3. 1 ~R 3 X 1 , X 2 R may be bonded to form a ring structure. 1 If there are multiple R 1 may be bonded to form a ring structure. 2 , R 3 The same is true for .)
[0022] X in the above general formula (1)1 , X 2 are the same or different and represent a nitrogen atom, an oxygen atom, a sulfur atom or a divalent linking group which may have a substituent. Examples of the divalent linking group include divalent hydrocarbon groups and groups in which some of the carbon atoms of a hydrocarbon group have been substituted with a heteroatom such as a nitrogen atom, an oxygen atom or a sulfur atom. The hydrocarbon group preferably has 1 to 6 carbon atoms, and more preferably has 1, 2 or 6 carbon atoms. The hydrocarbon group may be linear, branched, cyclic, or a combination thereof. The divalent hydrocarbon group may be an alkylene group, which is a saturated hydrocarbon group, or an unsaturated hydrocarbon group such as an alkenylene group or an alkynylene group. Specifically, the divalent hydrocarbon group is preferably one represented by the following formulas (2-1) to (2-4). In the following formulas (2-1) to (2-4), R represents a substituent. X, including R in (2-1) to (2-4), 1 , X 2 Specific examples of the substituent in R 1 ~R 3 Examples of the monovalent substituent include the same groups as those of the monovalent substituent of the above.
[0023] [ka]
[0024] In the above general formula (1), L represents a direct bond or a p-valent linking group. Note that L becomes a direct bond only when p is 2. Examples of the p-valent linking group include a nitrogen atom, an oxygen atom, a sulfur atom, a carbon atom, and also a group obtained by removing p hydrogen atoms from a hydrocarbon group or a group in which some of the carbon atoms of a hydrocarbon group have been substituted with a hetero atom such as a nitrogen atom, an oxygen atom, or a sulfur atom. When the p-valent linking group has a carbon atom, it preferably has 1 to 30 carbon atoms, and more preferably has 1 to 20 carbon atoms. The hydrocarbon group may be linear, branched, cyclic, or a combination thereof. The hydrocarbon group may be any of a saturated hydrocarbon group, an unsaturated hydrocarbon group, and an aromatic hydrocarbon group. Examples of aromatic hydrocarbon groups include groups formed by removing a hydrogen atom from an aromatic compound such as a benzene ring, a naphthalene ring, an anthracene ring, a tetracene ring, a pentacene ring, a triphenylene ring, a pyrene ring, a fluorene ring, or an indene ring.
[0025] R in the above general formula (1) 1 ~R 3 are the same or different and represent monovalent substituents. Examples of the monovalent substituent include a fluorine atom; a haloalkyl group such as a fluoromethyl group, a difluoromethyl group, or a trifluoromethyl group; a linear or branched alkyl group having 1 to 20 carbon atoms such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, or a tert-butyl group; a cyclic alkyl group having 5 to 7 carbon atoms such as a cyclopentyl group, a cyclohexyl group, or a cycloheptyl group; a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, an isobutoxy group, a tert-butoxy group, a pentyloxy group, a hexyloxy group, a heptyloxy group, or an oxy group. linear or branched alkoxy groups having 1 to 20 carbon atoms, such as octyloxy; a nitro group; a cyano group; an alkylamino group having an alkyl group having 1 to 10 carbon atoms, such as a methylamino group, an ethylamino group, a dimethylamino group, or a diethylamino group; a cyclic amino group, such as a pyrrolidino group, a piperidino group, or a morpholino group; a diarylamino group, such as a diphenylamino group or a carbazolyl group; an acyl group, such as an acetyl group, a propionyl group, or a butyryl group; an alkenyl group having 2 to 30 carbon atoms, such as a styryl group; a halogen atom such as a fluorine atom, or an alkyl group, alkoxy group, or amino group having 1 to 20 carbon atoms, an aryl group having 5 to 20 carbon atoms which may be substituted with (specific examples of the aryl group are the same as those of the aromatic hydrocarbon group described above); a heterocyclic group containing one or more of a nitrogen atom, a sulfur atom, and an oxygen atom which may be substituted with a halogen atom such as a fluorine atom, an alkyl group, an alkoxy group, an amino group, or the like having 1 to 20 carbon atoms (the heterocyclic group may be one consisting of only one ring, or may be a compound in which a plurality of compounds consisting of only one aromatic heterocycle are directly bonded to each other at one carbon atom, or may be a condensed heterocyclic group. Specific examples of the heterocyclic group include a thiophene ring, a furan ring, a phenyl ... Specific examples of aromatic heterocyclic groups include a pyrrole ring, a benzothiophene ring, a benzofuran ring, an indole ring, a dibenzothiophene ring, a dibenzofuran ring, a carbazole ring, a thiazole ring, a benzothiazole ring, an oxazole ring, a benzoxazole ring, an imidazole ring, a benzimidazole ring, a pyridine ring, a pyrimidine ring, a pyrazine ring, a pyridazine ring, a triazine ring, a quinoline ring, an isoquinoline ring, a quinoxaline ring, a benzothiadiazole ring, and a phenanthridine ring; an ester group, a thioether group, and the like, and groups formed by combining these groups.These groups may be substituted with a halogen atom, a hetero element, an alkyl group, an aromatic ring, or the like.
[0026] The compound represented by the above general formula (1) includes a compound having a structure represented by the following general formula (3) having only one phenanthroline skeleton, and this compound is also suitable as a material for the organic electron injection layer of the present invention.
[0027] [ka]
[0028] (In general formula (3), R 4 , R 5 m may be the same or different and represents a dialkylamino group or an alkoxy group. 4 , m 5 are the same or different and represent the number 1 or 2. 4 If there are multiple R 4 may be bonded to form a ring structure. 5 The same is true for .)
[0029] R in General (3) above 4 , R 5 are the same or different and represent a dialkylamino group or an alkoxy group. The dialkylamino group preferably has an alkyl group having 1 to 20 carbon atoms, such as a methyl group or an ethyl group. More preferably, the dialkylamino group has an alkyl group having 1 to 10 carbon atoms. The two alkyl groups in the dialkylamino group may have the same or different carbon numbers. Also preferred are amino groups in which two alkyl groups are linked, such as cyclic amino groups such as a piperidino group, a pyrrolidino group, or a morpholino group. The alkoxy group is R 1 ~R 3 is an alkoxy group.
[0030] In addition to compounds having only one phenanthroline skeleton, compounds having multiple phenanthroline skeletons such as those represented by the following formulas (4-1) to (4-4) are also considered to be effective in generating negative charges.
[0031] [ka]
[0032] Furthermore, p in the above general formula (1) represents a number from 1 to 4, and is preferably a number from 1 to 3. Specific examples of the compound in which p in general formula (1) is 1 include the compounds represented by the following formulas (5-1) to (5-9).
[0033] [ka]
[0034] In the above general formula (1), n 1 represents the number 0 or 1, and the compound represented by the above general formula (1) is 1 In one preferred embodiment of the present invention, the compound is a compound in which n in the general formula (1) is 0. 1 Specific examples of the compound in which is 0 include the compounds represented by the above formulas (5-1) to (5-6).
[0035] In addition, the compounds represented by the following formulas (5-10) to (5-65), which are included in the above general formula (1) and have a similar structure to the above, are also suitable.
[0036] [ka] [ka] [ka] [ka] [ka]
[0037] Furthermore, the material for the organic electron injection layer 5 may be any material that has a nitrogen atom capable of coordinating, and various compounds having the structures represented by the following formulae (5-66) to (5-68) as their skeletal structures may also be used. These compounds include compounds having the structures represented by the following formulae (5-66) to (5-68) as well as compounds having substituents in the structures represented by the following formulae (5-66) to (5-68). Examples of the substituents include R in the above-mentioned general formula (1). 1 ~R 3 The number of the substituents may be one or more. When there are more than one substituents, the substituents may be bonded to each other to form a ring structure.
[0038] [ka]
[0039] Furthermore, a hexahydropyrimidopyrimidine compound having a structure represented by the following general formula (6) can also be used as a material for the organic electron injection layer 5.
[0040] [ka]
[0041] (In general formula (6), R 6 represents an aromatic hydrocarbon group, an aromatic heterocyclic group, an aryl alkylene group, a divalent to tetravalent linear or cyclic hydrocarbon group, which may have a substituent, a group formed by combining two or more of these groups, or a group formed by combining one or more of these groups with a nitrogen atom. 2 is an integer from 1 to 4.)
[0042] It has been confirmed that the hexahydropyrimidopyrimidine compound having the structure represented by the above general formula (6) can coordinate with magnesium contained in the cathode 3, and has the effect of preventing reactions at the interface with oxygen or water entering from the outside, thereby enhancing the atmospheric stability of the element. Furthermore, the dipole generated by the interaction with the magnesium contained in the cathode 3 can result in improved electron injection from the cathode 3.
[0043] R in the above general formula (6) 6 represents an aromatic hydrocarbon group which may have a substituent, an aromatic heterocyclic group, an aryl alkylene group, a divalent to tetravalent chain or cyclic hydrocarbon group, a group formed by combining two or more of these groups, or a group formed by combining one or more of these groups with a nitrogen atom. The aromatic hydrocarbon group and aromatic heterocyclic group preferably have 3 to 30 carbon atoms, more preferably have 4 to 24 carbon atoms, and further preferably have 5 to 20 carbon atoms. Examples of aromatic hydrocarbon groups include compounds consisting of only one aromatic ring, such as benzene; compounds in which multiple aromatic rings, such as biphenyl and diphenylbenzene, are directly bonded to each other via one carbon atom; and groups formed by removing one to four hydrogen atoms from any of the aromatic rings of condensed ring aromatic hydrocarbon compounds, such as naphthalene, anthracene, phenanthrene, and pyrene. Examples of the aromatic heterocyclic group include compounds consisting of only one aromatic heterocycle, such as thiophene, furan, pyrrole, oxazole, oxadiazole, thiazole, thiadiazole, imidazole, pyridine, pyrimidine, pyrazine, and triazine; compounds in which a plurality of compounds consisting of only one aromatic heterocycle are directly bonded to each other via one carbon atom (such as bipyridine); and groups obtained by removing 1 to 4 hydrogen atoms from any of the aromatic heterocycles of condensed ring heteroaromatic hydrocarbon compounds, such as quinoline, quinoxaline, benzothiophene, benzothiazole, benzimidazole, benzoxazole, indole, carbazole, dibenzofuran, dibenzothiophene, acridine, and phenanthroline. The arylalkylene group includes a group formed by combining the above aromatic hydrocarbon group with an alkylene group having 1 to 3 carbon atoms. The divalent to tetravalent chain or cyclic hydrocarbon group preferably has 1 to 12 carbon atoms, more preferably has 1 to 6 carbon atoms, and further preferably has 1 to 4 carbon atoms. The chain hydrocarbon group may be either linear or branched. Also, R 6 may be a group formed by combining two or more of the above-mentioned aromatic hydrocarbon groups, aromatic heterocyclic groups, aryl alkylene groups, and divalent to tetravalent chain hydrocarbon groups. Furthermore, R 6 may be a group formed by combining one or more of the above aromatic hydrocarbon groups, aromatic heterocyclic groups, aryl alkylene groups, and divalent to tetravalent chain hydrocarbon groups with a nitrogen atom. Examples of such groups include groups formed by removing 1 to 4 hydrogen atoms from trialkylamines such as trimethylamine or triphenylamine.
[0044] The aromatic hydrocarbon group, aromatic heterocyclic group, or arylalkylene group may have one or more monovalent substituents. The monovalent substituent is R in the above general formula (1). 1 ~R 3 Specific examples of the monovalent substituent include the same as those given above.
[0045] In the above general formula (6), n 2 is an integer of 1 to 4, preferably 2 or 3. Specific examples of the hexahydropyrimidopyrimidine compound having the structure represented by the above general formula (6) include the compounds represented by the following formulas (7-1) to (7-34).
[0046] [ka] [ka] [ka] [ka] [ka]
[0047] The compound represented by the above general formula (6) can be synthesized by using a halogen compound having iodine, bromine, chlorine or fluorine and hexahydropyrimidopyrimidine as raw materials through Ullmann coupling reaction, Buchwald-Hartwig amination reaction, nucleophilic substitution reaction, or the like, as shown in the following formula (8).
[0048] [ka]
[0049] In addition, as long as it can be used as a ligand, examples include acetylacetonato derivatives in which not only nitrogen atoms but also oxygen atoms are the coordination elements. The average thickness of the organic electron injection layer 5 is preferably from 0.5 to 10 nm, more preferably from 1 to 5 nm, and further preferably from 1 to 5 nm. The average thickness of the organic electron injection layer 5 can be measured by, for example, a stylus step gauge or spectroscopic ellipsometry. Alternatively, the organic electron injection layer may be blended with the next layer, the electron transport layer 6 .
[0050] "Electron transport material" For the electron transport layer 6, any material that can be usually used as a material for an electron transport layer may be used, and can be used as necessary. Specifically, the material of the electron transport layer 6 may be a phosphine oxide derivative such as phenyl-dipyrenylphosphine oxide (POPy2), a pyridine derivative such as tris-1,3,5-(3'-(pyridin-3''-yl)phenyl)benzene (TmPhPyB), a quinoline derivative such as (2-(3-(9-carbazolyl)phenyl)quinoline (mCQ)), a pyrimidine derivative such as 2-phenyl-4,6-bis(3,5-dipyridylphenyl)pyrimidine (BPyPPM), a pyrazine derivative, or bathophenanthroline (BPhen). phenanthroline derivatives such as 2,4-bis(4-biphenyl)-6-(4'-(2-pyridinyl)-4-biphenyl)-[1,3,5]triazine (MPT); triazole derivatives such as 3-phenyl-4-(1'-naphthyl)-5-phenyl-1,2,4-triazole (TAZ); oxazole derivatives, oxadiazole derivatives such as 2-(4-biphenylyl)-5-(4-tert-butylphenyl-1,3,4-oxadiazole) (PBD); Imidazole derivatives such as tris(1-phenyl-1-H-benzimidazole) (TPBI), aromatic carboxylic anhydrides such as naphthalene-1,4,5,8-tetracarboxylic dianhydride and 3,4,9,10-perylenetetracarboxylic dianhydride, aromatic imide compounds such as N,N'-dimethyl-3,4,9,10-perylenetetracarboxylic dianhydride, compounds with carbonyl groups such as isoindigo derivatives, 2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione derivatives (diketopyrrolopyrroles), and toluxenone, naphtho[1 ,2-c:5,6-c']bis[1,2,5]thiadiazole, 1,2,5-thiadiazole derivatives such as benzo[c][1,2,5]thiadiazole, various metal complexes such as bis[2-(2-hydroxyphenyl)benzothiazolato]zinc (Zn(BTZ)2) and tris(8-hydroxyquinolinato)aluminum (Alq3), organic silane derivatives such as silole derivatives such as 2,5-bis(6'-(2',2''-bipyridyl))-1,1-dimethyl-3,4-diphenylsilole (PyPySPyPy), tris(2,4,6-trimethyl-3-(pyridin-3-yl)phenyl)borane (3TPYMB) and boron-containing compounds described in Japanese Patent Application No. 2012-228460, Japanese Patent Application No. 2015-503053, Japanese Patent Application No. 2015-053872, Japanese Patent Application No. 2015-081108 and Japanese Patent Application No. 2015-081109, and the like, and one or more of these can be used. In addition to the above materials, aromatic hydrocarbon compounds, which are various hydrocarbon compounds having an aromatic ring, compounds having a nitrogen-boron bond, π-electron-rich heteroaromatic compounds containing aromatic rings such as pyrrole rings, furan rings, and thiophene rings, and compounds containing silole rings can also be used. Among these materials for the electron transport layer 6, it is particularly preferable to use a phosphine oxide derivative such as POPy2, a metal complex such as Alq3, or a pyridine derivative such as TmPhPyB.
[0051] When the material of the organic electron injection layer 5 of the organic EL device of the present invention is mixed with the above-mentioned electron transport material, the electron transport layer 6 may not be required. In addition, a part of these materials may be used as a hole blocking material to form a hole blocking layer. Separately, any material that can be usually used may be used as the material of the hole blocking layer, and may be used as necessary. The average thickness of the electron transport layer 6 is not particularly limited, but is preferably from 10 to 150 nm, and more preferably from 20 to 100 nm. The average thickness of the electron transport layer 6 can be measured by a stylus step gauge or spectroscopic ellipsometry.
[0052] "Light-emitting layer" The material for forming the light-emitting layer 7 may be any material that can be normally used as the material for the light-emitting layer 7, or a mixture of these materials may be used. For example, the light-emitting layer 7 may contain bis[2-(2-benzothiazolyl)phenolato]zinc(II) (Zn(BTZ)2) and tris[1-phenylisoquinoline]iridium(III) (Ir(piq)3). For example, three-coordinate iridium complexes with 2,2'-bipyridine-4,4'-dicarboxylic acid as the ligand, such as factolys(2-phenylpyridine)iridium (Ir(ppy)3), 8-hydroxyquinoline aluminum (Alq3), tris(4-methyl-8-quinolinolato)aluminum(III) (Almq3), 8-hydroxyquinoline zinc (Znq2), (1,10-phenanthroline)-tris-(4,4,4-trifluoro-1-(2-thienyl)-butane-1,3-dionate)europium(III) (Eu(TT A) 3(phen)) and various metal complexes such as 2,3,7,8,12,13,17,18-octaethyl-21H,23H-porphine platinum(II); benzene-based compounds such as distyrylbenzene (DSB) and diaminodistyrylbenzene (DADSB); naphthalene-based compounds such as naphthalene and Nile Red; phenanthrene-based compounds such as phenanthrene; chrysene-based compounds such as chrysene and 6-nitrochrysene; perylene and N,N'-bis(2,5-di-t-butylphenyl)-3,4,9,10-perylene perylene compounds such as bis(trimethylsilyl)-dicarboximid (BPPC); coronene compounds such as coronene; anthracene compounds such as anthracene, bis(styrylanthracene); pyrene compounds such as pyrene; pyran compounds such as 4-(dicyanomethylene)-2-methyl-6-(para-dimethylaminostyryl)-4H-pyran (DCM); acridine compounds such as acridine; stilbene compounds such as stilbene; thiophene compounds such as 2,5-dibenzoxazolethiophene; benzoxazole Benzoxazole compounds such as benzimidazole;Benzothiazole compounds such as 2,2'-(para-phenylenedivinylene)-bisbenzothiazole;Butadiene compounds such as bistyryl(1,4-diphenyl-1,3-butadiene), tetraphenylbutadiene;Naphthalimide compounds such as naphthalimide;Coumarin compounds such as coumarin;Perinone compounds such as perinone;Oxadiazole compounds such as oxadiazole;Aldazine compounds;Examples of suitable compounds include cyclopentadiene compounds such as 1,2,3,4,5-pentaphenyl-1,3-cyclopentadiene (PPCP); quinacridone compounds such as quinacridone and quinacridone red; pyridine compounds such as pyrrolopyridine and thiadiazolopyridine; spiro compounds such as 2,2',7,7'-tetraphenyl-9,9'-spirobifluorene; metal or metal-free phthalocyanine compounds such as phthalocyanine (H2Pc) and copper phthalocyanine; and boron compound materials described in JP-A-2009-155325, JP-A-2011-184430, and JP-A-2011-6458.
[0053] The material forming the light-emitting layer 7 may be a low molecular weight compound or a high molecular weight compound. In the present invention, a low molecular weight material means a material that is not a high molecular weight material (polymer), and does not necessarily mean an organic compound with a low molecular weight. The average thickness of the light-emitting layer 7 is not particularly limited, but is preferably 10 to 150 nm, and more preferably 20 to 100 nm. The average thickness of the light-emitting layer 7 may be measured by a stylus-type step gauge, or may be measured by a quartz crystal thickness gauge during the deposition of the light-emitting layer 7.
[0054] "Hole transport layer" As the hole transporting organic material used in the hole transport layer 8, various p-type polymeric materials (organic polymers) and various p-type low molecular weight materials can be used alone or in combination.
[0055] Specifically, examples of the material of the hole transport layer 8 include N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (α-NPD), N4,N4'-bis(dibenzo[b,d]thiophen-4-yl)-N4,N4'-diphenylbiphenyl-4,4'-diamine (DBTPB), polyarylamine, fluorene-arylamine copolymer, fluorene-bithiophene copolymer, poly(N-vinylcarbazole), polyvinylpyrene, polyvinylanthracene, polythiophene, polyalkylthiophene, polyhexylthiophene, poly(p-phenylenevinylene), polythienylenevinylene, pyrene formaldehyde resin, ethylcarbazole formaldehyde resin or derivatives thereof. These materials of the hole transport layer 8 can also be used as a mixture with other compounds. An example of a mixture containing polythiophene that can be used as a material for the hole transport layer 8 is poly(3,4-ethylenedioxythiophene / styrenesulfonic acid) (PEDOT / PSS).
[0056] The average thickness of the hole transport layer 8 is not particularly limited, but is preferably from 10 to 150 nm, and more preferably from 20 to 100 nm. The average thickness of the hole transport layer 8 can be measured by, for example, a stylus step gauge or spectroscopic ellipsometry.
[0057] "Hole injection layer" The hole injection layer 9 may be made of an inorganic material or an organic material. Inorganic materials are more stable than organic materials, and therefore tend to have high resistance to oxygen and water compared to the case where an organic material is used.
[0058] The inorganic material is not particularly limited, but for example, one or more metal oxides such as vanadium oxide (V2O5), molybdenum oxide (MoO3), and ruthenium oxide (RuO2) can be used.
[0059] Examples of organic materials that can be used include low molecular weight materials such as dipyrazino[2,3-f:2',3'-h]quinoxaline-2,3,6,7,10,11-hexacarbonitrile (HAT-CN) and 2,3,5,6-tetrafluoro-7,7,8,8-tetracyano-quinodimethane (F4-TCNQ), as well as poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate (PEDOT:PSS).
[0060] The average thickness of the hole injection layer 9 is not particularly limited, but is preferably 1 to 1000 nm, and more preferably 5 to 50 nm. The average thickness of the hole injection layer 9 can be measured during deposition by a quartz crystal thickness gauge, a stylus step gauge, or spectroscopic ellipsometry.
[0061] "anode" Examples of materials that can be used for the anode 10 include ITO, IZO, Au, Pt, Cu, Ag, Al, and alloys containing these. Among these, it is preferable to use ITO, IZO, Au, or Al as the material for the anode 10.
[0062] The average thickness of the anode 10 is not particularly limited, but is preferably 10 to 1000 nm, and more preferably 30 to 200 nm. Even when an opaque material is used as the material for the anode 10, the anode can be used as a transparent anode in a top-emission organic EL device by, for example, setting the average thickness to about 10 to 30 nm. The average thickness of the anode 10 can be measured during the deposition of the anode 10 using a quartz crystal film thickness gauge.
[0063] "Sealing" The organic EL element 1 shown in FIG. 1 may be sealed, if necessary.
[0064] For example, the organic EL element 1 shown in Fig. 1 may be sealed with a sealing container (not shown) having a concave space for accommodating the organic EL element 1, and an adhesive for bonding the edge of the sealing container to the substrate 2. Alternatively, the organic EL element 1 may be accommodated in a sealing container, and sealed by filling it with a sealant made of an ultraviolet (UV) curable resin or the like. Alternatively, for example, the organic EL element 1 shown in Fig. 1 may be sealed with a sealing member made of a plate member (not shown) arranged on the anode 10 and a frame member (not shown) arranged along the edge of the plate member on the side facing the anode 10, and an adhesive for bonding between the plate member and the frame member and between the frame member and the substrate 2.
[0065] When the organic EL element 1 is sealed using a sealing container or a sealing member, a desiccant that absorbs moisture may be placed inside the sealing container or the sealing member. A material that absorbs moisture may be used as the sealing container or the sealing member. A space may be formed inside the sealed sealing container or the sealing member.
[0066] A resin material, a glass material, etc. can be used as a material for a sealing container or a sealing member used to seal the organic EL element 1 shown in Fig. 1. Examples of the resin material and the glass material used for the sealing container or the sealing member include the same materials as those used for the substrate 2.
[0067] In the organic EL device 1 of this embodiment, when the organic electron injection layer 5 is formed using an organic material having the coordination ability represented by the above general formula (1), excellent durability can be obtained compared to, for example, a device in which the electron injection layer is formed only with an alkali metal, which is a material that is unstable in the atmosphere. -4 ~10 -3 Order (g / m 2 / day), deterioration of the organic EL element 1 can be sufficiently suppressed. -3 Order (g / m 2It is possible to use a resin material with a thermal expansion coefficient of about 100 / day or less, and thus it is possible to realize an organic EL element 1 with excellent flexibility.
[0068] "Manufacturing method for organic EL elements" Next, as an example of a method for manufacturing an organic EL element of the present invention, a method for manufacturing an organic EL element 1 having an inverted structure shown in Fig. 1 will be described, but the organic EL element of the present invention may have a conventional forward structure. In that case, for example, it is sufficient to laminate the anode and hole injection layer so that the configuration is reversed, and there is no particular limitation on the film formation method. To manufacture the organic EL element 1 shown in FIG. 1, first, a cathode 3 is formed on a substrate 2 . The cathode 3 can be formed by a sputtering method, a vacuum deposition method, a sol-gel method, a spray pyrolysis (SPD) method, an atomic layer deposition (ALD) method, a vapor phase deposition method, a liquid phase deposition method, etc. The cathode 3 may be formed by bonding a metal foil. Next, the organic electron injection layer 5 is formed on the cathode 3 . The organic electron injection layer 5 is formed by using, for example, a vacuum deposition method. Next, on the organic electron injection layer 5, the electron transport layer 6, the light emitting layer 7, and the hole transport layer 8 are formed in this order. The methods for forming the electron transport layer 6, the light emitting layer 7, and the hole transport layer 8 are not particularly limited, and various conventionally known formation methods can be used appropriately in accordance with the properties of the materials used for the electron transport layer 6, the light emitting layer 7, and the hole transport layer 8, respectively. Next, the hole injection layer 9 and the anode 10 are formed in this order on the hole transport layer 8. For these layers as well, various conventionally known formation methods can be appropriately used in accordance with the properties of the materials used for each. By the above steps, the organic EL element 1 shown in FIG. 1 is obtained.
[0069] "Sealing method" The organic EL device 1 shown in FIG. 1 can be encapsulated using a conventional method used for encapsulating organic EL devices. EXAMPLES
[0070] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "%" means "mol %".
[0071] (Synthesis Example 1) The compound represented by the following formula (9) was synthesized by the method shown below.
[0072] [ka]
[0073] In a 100 mL round-bottom flask, a mixture of 4,7-dichloro-1,10-phenanthroline (3.00 g) and pyrrolidine (19.5 mL) was heated to reflux in an oil bath at 100°C for 1 hour. The mixture was returned to room temperature and concentrated under reduced pressure, water was added, and the precipitated solid was filtered out by ultrasonic treatment. The obtained solid was dried under reduced pressure and then dissolved in methanol (100 mL). Activated carbon was added to the mixture and stirred at room temperature for 1 hour, after which the insoluble matter was filtered off. The filtrate was concentrated under reduced pressure, and the obtained solid was recrystallized from methanol (9 mL). The obtained solid was washed with a small amount of methanol and dried under reduced pressure to obtain the compound represented by formula (9) (1.69 g, 44%) as a white solid.
[0074] Example 1 [Step 1] Barrier film manufactured by Oike Kogyo (PT7 / 25GT3: thickness 25 μm, WVTR: 4 × 10 -3 g / m 2 A resist material was applied onto the substrate (1 / day) to form a film, and zinc oxide was deposited to a thickness of 24 nm using a sputtering device to form a metal oxide layer 4. [Step 2] Next, in order to form a layer of 10 nm in total thickness containing silver and magnesium in a volume ratio of 70:30 as the cathode 3, the substrate that has been processed in [Step 1] is introduced into a vacuum device and 5 × 10 -5 The pressure was reduced to 0.1 Pa or less, and a film was formed by vacuum deposition. [Step 3] Next, the material of the above formula (9), which is a material for organic electron injection layers, was laminated by a vacuum deposition method to a thickness of 3 nm as the organic electron injection layer 5, KHLHEI-02 manufactured by Chemipro Chemical Co., Ltd., which is an electron transport material, was laminated by a thickness of 15 nm as the electron transport layer 6, KHLHS-04 manufactured by Chemipro Chemical Co., Ltd., was laminated by a thickness of 15 nm as the hole blocking layer 11, KHLHS-03, KHLHS-04, and KHLDG-01 manufactured by Chemipro Chemical Co., Ltd. were laminated by co-deposition to a thickness of 35 nm as the light-emitting layer 7, and KHLHS-03 manufactured by Chemipro Chemical Co., Ltd. was laminated by a vacuum deposition method to a thickness of 25 nm as the hole transport layer 8. [Step 4] Next, the hole injection layer 9 was formed on the hole transport layer 8. Here, molybdenum oxide was formed to a thickness of 10 nm by a vacuum deposition method, which is a gas phase film formation method. [Step 5] Next, as the final step, an anode 10 was formed on the hole injection layer 9. Here, an aluminum film was formed by vacuum deposition so as to have a thickness of 200 nm. Furthermore, a barrier film (thickness: 25 μm, WVTR: 4×10) manufactured by Oike Kogyo Co., Ltd. was formed on the anode. -3 g / m 2 Sealing was carried out at 100° C. / day. By the above steps [Step 1] to [Step 5], a film organic electroluminescence device having the configuration shown in Fig. 4 was produced. The thickness was about 98 µm. [Step 6] The atmospheric stability of the fabricated organic electroluminescent device was evaluated by storing it in an environment of 85°C and 85% humidity. The results are shown in Figure 6. No dark spots were observed even after 65 hours.
[0075] Example 2 An organic electroluminescence device was produced in the same manner as in Example 1, except that [Step 2] in Example 1 was changed to the following [Step 2-2]. As [Step 6], the atmospheric stability of the organic electroluminescence device was evaluated using the same method as in Example 1, and the results are shown in Figure 7. No dark spots were observed even after 65 hours. [Step 2-2] Next, in order to form a layer of 10 nm in total thickness containing silver and magnesium in a volume ratio of 95:5 as the cathode 3, the substrate processed in [Step 1] is introduced into a vacuum device, and 5 × 10 -5 The pressure was reduced to 0.1 Pa or less, and a film was formed by vacuum deposition.
[0076] Example 3 An organic electroluminescence device was produced in the same manner as in Example 1, except that [Step 2] in Example 1 was changed to the following [Step 2-3]. As [Step 6], the atmospheric stability of the organic electroluminescence device was evaluated using the same method as in Example 1, and the results are shown in Figure 8. No dark spots were observed even after 65 hours. [Step 2-3] Next, in order to form a layer of 10 nm in total thickness containing silver and magnesium in a volume ratio of 97:3 as the cathode 3, the substrate processed in [Step 1] is introduced into a vacuum device, and 5 × 10 -5 The pressure was reduced to 0.1 Pa or less, and a film was formed by vacuum deposition.
[0077] Example 4 An organic electroluminescence device was produced in the same manner as in Example 1, except that [Step 2] in Example 1 was changed to the following [Step 2-4]. As [Step 6], the atmospheric stability of the organic electroluminescence device was evaluated using the same method as in Example 1, and the results are shown in Figure 9. No dark spots were observed even after 65 hours. [Step 2-4] Next, in order to form a layer of 25 nm in total thickness containing silver and magnesium in a volume ratio of 95:5 as the cathode 3, the substrate processed in [Step 1] is introduced into a vacuum device, and 5 × 10 -5 The pressure was reduced to 0.1 Pa or less, and a film was formed by vacuum deposition.
[0078] Example 5 An organic electroluminescence device was produced in the same manner as in Example 1, except that [Step 2] in Example 1 was changed to the following [Step 2-5]. In [Step 6], the atmospheric stability of the organic electroluminescence device was evaluated by the same method as in Example 1. No dark spots were observed even after 65 hours. [Step 2-5] Next, in order to form a layer of 35 nm in total thickness containing silver and magnesium in a volume ratio of 95:5 as the cathode 3, the substrate processed in [Step 1] is introduced into a vacuum device, and 5 × 10 -5 The pressure was reduced to 0.1 Pa or less, and a film was formed by vacuum deposition.
[0079] Comparative Example 1 An organic electroluminescence device was produced in the same manner as in Example 1, except that [Step 2] in Example 1 was changed to the following [Steps 2-6]. As [Step 6], the atmospheric stability of the organic electroluminescence device was evaluated by the same method as in Example 1, and the results are shown in Figure 10. Dark spots were observed after 65 hours. [Step 2-6] Next, in order to form a layer of 10 nm in total thickness containing silver and magnesium in a volume ratio of 50:50 as the cathode 3, the substrate processed in [Step 1] is introduced into a vacuum device and 5 × 10 -5 The pressure was reduced to 0.1 Pa or less, and a film was formed by vacuum deposition.
[0080] Comparative Example 2 An organic electroluminescence device was produced in the same manner as in Example 1 except that [Step 2] in Example 1 was changed to the following [Step 2-7] [Step 6], and the atmospheric stability of the organic electroluminescence device was evaluated in the same manner as in Example 1. After 65 hours, no light emission was observed. [Step 2-7] Next, in order to form a layer of 10 nm in total thickness containing silver and magnesium in a volume ratio of 99:1 as the cathode 3, the substrate processed in [Step 1] is introduced into a vacuum device, and 5 × 10 -5 The pressure was reduced to 0.1 Pa or less, and a film was formed by vacuum deposition.
[0081] Comparative Example 3 A film organic electroluminescence device having the configuration shown in FIG. 5 was produced in the same manner as in Example 1, except that [Step 2] in Example 1 was changed to the following [Step 2-8]. In [Step 6], the atmospheric stability of the organic electroluminescence device was evaluated using the same method as in Example 1, and the results are shown in FIG. 11. Many dark spots were observed after 65 hours. [Step 2-8] Next, in order to form 9 nm of silver as the cathode 3 and 1 nm of magnesium as the metal electron injection layer 12, the substrate that has been processed in [Step 1] is introduced into a vacuum device and 5×10 -5 The pressure was reduced to below 1 Pa, and a film was formed by vacuum deposition. As a result, magnesium in the cathode was separated as the metal electron injection layer 12, and a laminated element was completed.
[0082] Comparative Example 4 An organic electroluminescence device was produced in the same manner as in Example 1, except that [Step 2] in Example 1 was changed to the following [Step 2-9]. In [Step 6], the atmospheric stability of the organic electroluminescence device was evaluated in the same manner as in Example 1. After 65 hours, no light emission was observed. [Step 2-9] Next, in order to form a layer of 45 nm in total thickness containing silver and magnesium in a volume ratio of 95:5 as the cathode 3, the substrate processed in [Step 1] is introduced into a vacuum device, and 5 × 10 -5 The pressure was reduced to 0.1 Pa or less, and a film was formed by vacuum deposition.
[0083] The initial light emitting characteristics of the devices of Examples 1 to 5 and Comparative Examples 1 to 4 are as shown in Table 1 below.
[0084] [Table 1]
[0085] In addition, from the results of the atmospheric stability test under conditions of 85°C and 85% humidity, it was found that there was no problem with the magnesium ratio if it was 30% or less, but if it was increased to 50%, there was a problem in terms of transparency and atmospheric stability. Regarding the lower limit, it was found that although the characteristics were expressed without any problem at 1% at the initial stage, a higher ratio was necessary if high atmospheric stability was required. As shown in Example 3, it was confirmed that high atmospheric stability was obtained at a ratio of 3%. Regarding the film thickness, there were no problems with both the initial characteristics and atmospheric stability up to 35 nm, but when it reached 45 nm, the occurrence of dark spots was observed in the atmospheric stability. As shown in the results of the examples, there was no problem with the lower limit up to 10 nm. Regarding the film thickness, it was confirmed that it was possible to form a film without thickness variation up to 7 nm, and there was no problem. [Explanation of symbols]
[0086] 1: organic EL element, 2: substrate, 3: cathode, 4: metal oxide layer, 5: organic electron injection layer, 6: electron transport layer, 7: light-emitting layer, 8: hole transport layer, 9: hole injection layer, 10: anode, 11: hole blocking layer, 12: metal electron injection layer
Claims
1. An organic electroluminescent device having at least a pair of electrodes and an organic layer therebetween, The organic electroluminescent device has a cathode which is a layer containing magnesium and silver and / or aluminum, in which the volume ratio of magnesium is 2% or more and 30% or less and has an average thickness of 40 nm or less, and an organic electron injection layer adjacent to the cathode which contains an organic material capable of forming a coordinate bond to a metal atom (excluding those in which the organic material contained in the organic electron injection layer contains a metal atom capable of forming a coordinate bond).
2. The organic electroluminescence device according to claim 1 , wherein the organic electroluminescence device is an element in which a cathode is formed on a substrate.
3. A display device comprising the organic electroluminescent device according to claim 1 or 2.
4. A lighting device comprising the organic electroluminescent device according to claim 1 .
Citation Information
Patent Citations
Organic compound, application thereof and organic electroluminescent device containing the compound
CN111943949A
Organic electroluminescent apparatus, its manufacturing method and electronic apparatus
JP2005093418A
Organic thin film light emitting element, display device, electronic apparatus, and manufacturing method of organic thin film light emitting element
JP2009070954A
Organic electroluminescence device and method of manufacturing the same, and electronic apparatus
JP2010067718A
Organic electroluminescent element material and organic electroluminescent element
JP2017157743A